STRATEGIES FOR USING PROFIT AND CASH FLOW STATEMENTS IN ASSESSING THE FINANCIAL PERFORMANCE OF PRIVATE BANK COMPANIES ON THE INDONESIA STOCK EXCHANGE - Majied Sumatrani Saragih, Maulana (CV. Radja Publika, 2021)
This study aims to find out how the Strategy for Using Profit and Cash Flow Statements on the Financial Performance of Indonesian Private Banks Listed on the Indonesia Stock Exchange. The research method used is quantitative data method. While the data used is secondary data. The data analysis method in this study uses multiple linear regression analysis to obtain a comprehensive picture of the effect of the Profit Usage variable on Financial Performance by using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of hypothesis testing using multiple regression analysis and t test show that: The use of profit (X1) has a positive and significant effect on Financial Performance (Y). In other words, it means, the use of profit has a positive and significant effect on financial performance. Cash Flow (X2) has no effect on Financial Performance (Y). In other words, it means, Cash Flow has no positive and significant effect on Financial Performance. Use of Profit (X1), Cash Flow Variable (X2), have a significant effect simultaneously (simultaneously) on the Financial Performance Variable (Y).